Distribution of Corneal Geometric Landmarks and Relationship Between Their Distances and Biomechanical Parameters in the Development of Keratoconus - Tian, Lei; Zhang, Hui; Guo, Li-Li; Qin, Xiao; Zhang, Di; Li, Lin; Wu, Ying; Jie, Ying; Zhang, Haixia (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: To analyze the changes in coordinates and distances among three typical geometric landmarks of the cornea, namely, the thinnest point (TP), maximum curvature (Kmax), and corneal apex (AP) during the development of keratoconus, and explore the potential relationship between these changes and the abnormalities of corneal biomechanics. Methods: Normal eyes (n = 127), clinical keratoconic eyes (CKC, n = 290), and the eyes of forme fruste keratoconus (FFKC, n = 85) were included, and CKC group was classified into four grades based on the Topographic Keratoconus Classification (TKC) provided by Pentacam. The differences among the above-mentioned six groups were been analyzed. Spearman’s rank correlation test was performed to choose several dynamic response parameters that could best reflect the changes of corneal biomechanical characteristics during the progression of the disease, and the Pearson’s or Spearman’s correlation test was conducted to determine the association between the three distances (DKmax-AP, DTP-AP, DKmax-TP) and the selected biomechanical parameters in each grade. In addition, by flipping the X coordinate of the left eye on the vertical axis to reflect the direction of the right eye, the coordinates of TP and Kmax in different developmental grades were highlighted. Results: There were 9 biomechanical parameters output by Corvis ST, which were strongly correlated with the developmental grades (|r|  0.6). From CKC stage II, the three geometric landmark distances commenced to correlate with the corneal biomechanical parameters. From normal cornea to CKC stage IV, the coordinates of Kmax were gradually concentrated from dispersion, and finally tended to the inferior temporal region, while the coordinates of TP were always concentrated in the inferior temporal region. Although both DKmax-AP and DKmax-TP seemed to decrease gradually, the distance between the point of Kmax and TP tended to be shorter. Conclusions: CBI, SPA1, IR, DA Ratio 2, ARTh, MIR, Radius, Pachy and DA Ratio 1, the nine parameters can better represent the changes of biomechanical properties from normal cornea to keratoconus. During the progression of disease, Kmax may gradually approach to TP, and weakening of corneal biomechanics may be accompanied by the coalescence of stress positions of typical geometric landmarks.